DOP62 A novel formulation of CT-P13 (infliximab biosimilar) for subcutaneous administration: 1-year result from a Phase I open-label randomised controlled trial in patients with active Crohn's disease. (25th January 2019) - Reinisch, W; Jang, B I; Borzan, V; Lahat, A; Pukitis, A; Osipenko, M; Mostovoy, Y; Schreiber, S; Ben-Horin, S; Lee, S J; Suh, J H; Lee, S G; et al.
Abstract: Background: Efficacy and safety of new subcutaneous (SC) formulation of CT-P13 (CT-P13 SC) up to Week 30 were comparable with intravenous (IV) formulation in both patients with Crohn's disease 1 (CD) and rheumatoid arthritis. 2 The aim of this study was to report pharmacokinetics (PK), efficacy and overall safety of CT-P13 SC in patients with CD throughout the 1-year treatment period. Methods: Patients with moderate-to-severe CD (CDAI score 220–450) were administered CT-P13 IV 5 mg/kg at Weeks 0 and 2, and randomised into four cohorts at Week 6. Cohort 1 received CT-P13 IV 5 mg/kg every 8 weeks and Cohorts 2–4 received CT-P13 SC 120 mg, 180 mg, and 240 mg, , respectively, every 2 weeks up to Week 54. Blood samples were collected before study drug administration at each visit and drug levels were determined by electrochemiluminescent assay. Efficacy parameters of CDAI-70 response, clinical remission (CDAI<150), endoscopic response and remission, and overall safety were evaluated. Results: In total, 44 patients were randomly assigned to 4 cohorts (1:1:1:1 ratio). Overall clinical response results were comparable between IV and SC cohorts after randomisation at Week 6 up to Week 30, whereas clinical remission appears to be numerically higher in the SC cohorts at Week 54. (Table 1). The mean Ctrough (pre-dose serum concentration of CT-P13 before next dose injection) in the SC cohorts throughout the study visits were higher than those of IV cohort after randomisation. Ctrough values increased with SC dose and were substantially greater than the target therapeutic concentration (5 μg/ml) 3 throughout the study period (Figure 1). Safety profiles for CT-P13 SC cohorts were also comparable to the IV cohort. In total, injection site reactions were reported in 11.4% of the patients, but all cases were of Grade 1 or 2 in intensity (Table 1). Conclusions: The results from 1-year treatment suggest similar efficacy and safety of CT-P13 SC to CT-P13 IV. The mean serum concentration in all SC cohorts consistently exceeded the threshold of target therapeutic concentration. These results show that the novel SC formulation of CT-P13 may expand treatment options for use of infliximab biosimilar by providing high consistency in drug exposure during maintenance treatment. References 1. Schreiber S, Jang BI, Borzan V, et al . Tu2018 – novel formulation of CT-P13 (infliximab biosimilar) for subcutaneous administration: initial results from a Phase I open-label randomized controlled trial in patients with active Crohn's disease. Gastroenterology 2018;154;S1371. 2. Westhovens R, Yoo DH, Jaworski J, et al. THU0191 – novel formulation of CT-P13 for subcutaneous administration in patients with rheumatoid arthritis: initial results from a phase I/III randomised controlled trial. Ann Rheum Dis 2018;77(Suppl 2). 3. Vaughn BP, Sandborn WJ, Cheifetz AS.. Biologic concentration testing in inflammatory bowel disease. Inflamm Bowel Dis 2015;21:1435–42.